2009
DOI: 10.1111/j.1468-2982.2009.01999.x
|View full text |Cite
|
Sign up to set email alerts
|

Migraines with and without aura and their response to preventive therapy with topiramate

Abstract: Data from the Prolonged Migraine Prevention (PROMPT) with Topiramate trial were evaluated post hoc to determine whether topiramate could prevent migraine auras, and whether its efficacy in preventing migraine headaches was similar in patients with (MA; n = 269) and without (MoA; n = 542) aura. Migraines and auras were recorded during prospective baseline, 6-month open-label (OL) topiramate and 6-month double-blind (DB), placebo-controlled phases. In the last 28 OL days, migraines without aura and migraine aura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 33 publications
(46 reference statements)
0
25
0
1
Order By: Relevance
“…Several post hoc subgroup analyses of topiramate versus placebo provided inconsistent efficacy evidence regarding aura. 95,96 …”
Section: Drug Effect Modification By Select Patient Characteristicsmentioning
confidence: 99%
“…Several post hoc subgroup analyses of topiramate versus placebo provided inconsistent efficacy evidence regarding aura. 95,96 …”
Section: Drug Effect Modification By Select Patient Characteristicsmentioning
confidence: 99%
“…These results contradict the perception stated in many published reports (9,11,24,25), and therefore questions the validity of excluding migraines with aura in the proposed ICHD-II definition of MRM. The discrepancy may be explained by the fact that, in the present study at least, only one-third of patients had migraine with aura, in whom only one-third of migraines were actually preceded by an aura (21). The high likelihood (89%) that any new migraine will be one without aura, therefore, might have led others to conclude that the extra migraines observed during the PMP were all migraines without aura.…”
Section: Discussionmentioning
confidence: 72%
“…However, the mechanism underlying its action in migraine is unknown [90]. On the basis of its rational of use [49], topiramate should have shown particular efficacy against migraine aura, which has not been demonstrated [50,51]. Its efficacy in migraine prevention is comparable to the other drugs for prophylaxis [91].…”
Section: Expert Opinionmentioning
confidence: 90%
“…However, a first trial on 12 patients showed that there was no statistically significant decline in the frequency and duration of aura during the 6 months of topiramate treatment compared with baseline values [50]. Even a post hoc analysis of data from the PROMPT study [44] found that there were no statistically significant changes in number of auras between placebo and topiramate groups [51].…”
Section: Pharmacokineticsmentioning
confidence: 96%
See 1 more Smart Citation